Patterns of early adolescent sex and implications for HIV/AIDS risk prevention : a contextual study in the Amatole Basin, Eastern Cape - Ntlabati, Pumla L (Rhodes University, Faculty of Humanities, Department of Psychology, 2003)
This study involves an analysis of accounts of first and subsequent early sexual experiences in a deep rural area of the Eastern Cape in South Africa over the last forty years. Through interviews and focus group discussions, the enculturation of youth into sexual activity in the community of interest is explored. The study looks into sexual experiences from childhood, through early adolescence to adults of up to sixty five years old, allowing an analysis of the changing forms of sexual experimentation and sexual debut in this context. Contextual factors mediating these changes are explored, with special emphasis on the changing regulatory practices around early sexual experiences and the effect thereof on behaviors connected to HIV infection risk. Practices that were previously important mediators of sexual behavior were: anxiety about the social consequences of pregnancy, which was previously a significant disincentive to sexual intercourse; men's previous acceptance of the need to practice non-penetrative forms of sex and girls postponing sexual debut for as long as possible. All these were culturally endorsed, but are now noted to have changed due to changes in the regulatory practices surrounding youth sexuality. The context of early sexual experiences and the surrounding cultural practices have also changed significantly, and this needs to be taken into account in understanding receptivity to condom use messages. Implications for HIV/AIDS prevention are discussed. Among other interventions, the study describes a participatory, community-based, multi-sectoral approach that takes social conditions into account as a way of empowering the community to strengthen its response to the pandemic. This incorporates different sectors of the community, including youth, parents, religious and traditional leaders, and various other structures, services and institutions that make up the community.
Keywords: Teenagers -- Sexual behavior; Teenagers -- Health and hygiene -- South Africa -- Eastern Cape; Teenagers -- Diseases -- South Africa -- Eastern Cape; Sexually transmitted diseases -- South Africa -- Eastern Cape; AIDS (Disease) -- South Africa -- Eastern Cape; AIDS (Disease) in adolescence -- South Africa -- Eastern Cape -- Attitudes; AIDS (Disease) -- Prevention -- South Africa --Eastern Cape